Rancang Bangun E-Commerce Menggunakan Framework Codeigniter (Ci) Dengan Php Pada Tang Kawi Jaya - Tri Setyo Slamet; Annisa Tsamratul"ain (Indonesian Journal of Thousand Literacies, 2025)
The development of information technology encourages business actors to optimize business processes through digital systems, including sales and marketing activities. Abadi Battery is an automotive battery store that still conducts its business processes conventionally through a physical store. This condition causes several problems, such as limited product information, ordering processes that require customers to visit the store directly, manual reporting, and the lack of digital promotional activities. This study aims to design an e-commerce website using the CodeIgniter framework and PHP programming language as a digital sales solution for Abadi Battery. The research methods include observation, interviews, documentation, literature review, analysis of the existing system, system design, and implementation. The analysis and design tools used include Activity Diagram, Fishbone Diagram, Business Model Canvas, Use Case Diagram, Class Diagram, and user interface design. The results show that the designed e-commerce system provides product catalogs, product details, stock information, shopping carts, checkout, payment confirmation, transaction management, sales reports, payment reports, shipping reports, promotional strategies, and Search Engine Optimization implementation. The system helps improve transaction management efficiency, expand marketing reach, and make it easier for customers to obtain information and place orders online